2018
DOI: 10.1111/risa.13215
|View full text |Cite
|
Sign up to set email alerts
|

An Agent‐Based Model for Pathogen Persistence and Cross‐Contamination Dynamics in a Food Facility

Abstract: We used an agent-based modeling (ABM) framework and developed a mathematical model to explain the complex dynamics of microbial persistence and spread within a food facility and to aid risk managers in identifying effective mitigation options. The model explicitly considered personal hygiene practices by food handlers as well as their activities and simulated a spatially explicit dynamic system representing complex interaction patterns among food handlers, facility environment, and foods. To demonstrate the ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…FDA‐Melon QRA‐EC used the Agent‐Based Modeling (ABM) framework presented in Mokhtari and Van Doren (2019) to describe fresh‐cut melon processing steps including initial cleaning, transfer on conveyor belts, automated peeling, manual cutting and seeds removal, automated chunking, and manual product assembly (Figure 1). The processing module primarily focused on the cross‐contamination between food handlers, processing equipment surfaces, and melons (whole and cut melons).…”
Section: Methodsmentioning
confidence: 99%
“…FDA‐Melon QRA‐EC used the Agent‐Based Modeling (ABM) framework presented in Mokhtari and Van Doren (2019) to describe fresh‐cut melon processing steps including initial cleaning, transfer on conveyor belts, automated peeling, manual cutting and seeds removal, automated chunking, and manual product assembly (Figure 1). The processing module primarily focused on the cross‐contamination between food handlers, processing equipment surfaces, and melons (whole and cut melons).…”
Section: Methodsmentioning
confidence: 99%
“…Mokhtari et al [5] developed an agent-based model of microbial persistence and spread in food facilities, simulating a spatially dynamic system representing the hygiene behavior of food handlers and their interactions between the facility environment and food products. Experimental results showed that areas not in direct contact with food (loading docks and toilets) could act as contamination sites and recontaminate regions in direct contact with food.…”
Section: Related Workmentioning
confidence: 99%
“…Most cross‐contamination studies rely on mixing inoculated and noninoculated produce and further enumeration (Nou & Luo, 2010). In the absence of reliable pathogen cross‐contamination detection systems in fresh produce, probabilistic system models (Mishra, Pang, Buchanan, Schaffner, & Pradhan, 2017), mechanistic models (Munther, Luo, Wu, Magpantay, & Srinivasan, 2015); risk assessment models (Perez‐Rodríguez, Campos, Ryser, & Buchholz, 2011) and other mathematical models that include the use of agent‐based frameworks (Mokhtari, Oryang, Chen, Pouillot, & Doren, 2018; Mokhtari & Van Doren, 2019; Zoellner, Jennings, Wiedmann, & Ivanek, 2019) have become important information tools.…”
Section: Introductionmentioning
confidence: 99%